2021
DOI: 10.1182/blood-2021-152767
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Prolonged Response after Stopping Thrombopoietin-Receptor Agonists Treatment in Primary Immune Thrombocytopenia (ITP): Results from a Nationwide Prospective Multicenter Interventional Study (STOPAGO)

Abstract: Background: Thrombopoietin receptor agonists(TPO-RAs) have been thought to play only a supporting role in ITP management. Several retrospective studies and a recent prospective study have reported unexpected cases of durable remission after TPO-RAs discontinuation in adult ITP in up to 30%. However, newly diagnosed ITP cases for which spontaneous remission may occur have been included in most of these studies. Thus, the main purpose of this study was to determine the proportion of patients with either persiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 0 publications
0
10
0
2
Order By: Relevance
“…Although TPO-RAs are not regarded as curative agents, somewhat unexpectedly, approximately 10–50% of patients after extended TPO-RA exposure are able to taper and eventually discontinue treatment without relapse [ 135 137 ]. Nevertheless, predictors of long-term response after TPO-RA discontinuation are lacking, but progressive tapering may be preferentially attempted in patients with a stable CR [ 137 ].…”
Section: Subsequent Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although TPO-RAs are not regarded as curative agents, somewhat unexpectedly, approximately 10–50% of patients after extended TPO-RA exposure are able to taper and eventually discontinue treatment without relapse [ 135 137 ]. Nevertheless, predictors of long-term response after TPO-RA discontinuation are lacking, but progressive tapering may be preferentially attempted in patients with a stable CR [ 137 ].…”
Section: Subsequent Treatmentmentioning
confidence: 99%
“…Although TPO-RAs are not regarded as curative agents, somewhat unexpectedly, approximately 10–50% of patients after extended TPO-RA exposure are able to taper and eventually discontinue treatment without relapse [ 135 137 ]. Nevertheless, predictors of long-term response after TPO-RA discontinuation are lacking, but progressive tapering may be preferentially attempted in patients with a stable CR [ 137 ]. In an expert consensus based on the RAND/UCLA modified Delphi method, TPO-RAs can be tapered in patients with normal or above normal platelet counts, no history of major bleeding, and no requirement for an intensification of treatment in the past 6 months; meanwhile, duration of ITP and TPO-RA taking as well as time to response (TTR) after treatment does not affect the decision on TPO-RA tapering [ 138 ].…”
Section: Subsequent Treatmentmentioning
confidence: 99%
“…Various guides and reviews support the discontinuation of TPO-RA [12][13][14][15][16][17]36] when there is lack of efficacy, there are unacceptable side effects (e.g., thrombosis, bone marrow fibrosis or hepatotoxicity) or successful remission after treatment is observed with the use of this type of treatment. It is worth noting here the new, interesting initiatives (iROM1 and iROM2 studies) taken by the Swiss group [37].…”
Section: Tapering and Srot Tpo-ras: Major Publications Clinical Appro...mentioning
confidence: 99%
“…Here, we describe all major routine clinical practice studies and reviews reporting on the current position in relation to this topic [7,8,11]. Four important studies also deserve to be considered in detail: the Italian prospective experience regarding discontinuation in an early phase (newly diagnosed/chronic) of immune thrombocytopenia ITP [9], the French STOP-AGO trial [12], the International Taper trial [13] and the American Boston experience [14]. Three Delphi-based recommendations (Spanish, UK and Italian consensus) will also be reviewed [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated a greater than 50% successful discontinuation rate when at least 2-3 months of stable TPO-RA dosing, no bleeding, and a platelet count >100x10 9 /L were required for the discontinuation attempt. 82 Patients were on romiplostim a median of 12 months before tapering; the doses administered were higher than normal to obtain stable counts >100x10 9 /L. The tapering protocol was at 2-weekly intervals for a total of not more than 2 months of tapering.…”
Section: Section Iii: Second-line Treatment Of Immune Thrombocytopeni...mentioning
confidence: 99%